Neural correlates of social exclusion in individuals with excessive smartphone use - Henemann, Gudrun Maria; Schmitgen, Mike; Haage, Sophie H.; Rosero, Jakob P.; Bach, Patrick; Wolf, Nadine D.; Koenig, Julian; Wolf, Robert Christian (Computers in human behavior, 2026)
Introduction - Excessive smartphone use (ESU) is increasingly recognized as a condition closely resembling other addictive disorders. While neuroscientific research on ESU has largely focused on reward and cognitive-control networks, the socio-cognitive domain has received comparatively little attention. In this context, social exclusion represents a particularly relevant construct, as digital connectivity has become central to maintaining a sense of social belonging. - Methods - To fill this gap, we investigated neural correlates of social exclusion in individuals with (n = 23) and without ESU (n = 18), using fMRI and the Cyberball paradigm. We also explored associations between brain activity and degrees of ESU and used standardized neurotransmitter maps to examine neural correlates involved in the processing of social exclusion. - Results - Between-group comparisons indicated heightened neural activity in the ESU group in the right middle cingulate cortex (MCC) extending into the right superior frontal cortex. By contrast, individuals without ESU showed increased activity in the left superior parietal cortex (SPC). Correlations between cross-modal brain activity and neurotransmitter maps highlighted the significant role played by dopaminergic and serotonergic transmission. Additionally, activity within the left SPC correlated positively with the “functional impairment” sub-score of the Smartphone Addiction Inventory. - Conclusion - Neural activity during social exclusion differs in individuals with and without ESU. Hyperactivation of the MCC indicates heightened sensitivity to social exclusion in ESU, underscoring its relevance within a socio-cognitive framework of the condition. These findings emphasize the importance of further investigating how the anticipation, avoidance, or experience of social exclusion may contribute to the development and maintenance of ESU.
Online verfügbar: 12.November 2025, Artikelversion: 21. November 2025
Gesehen am 26.01.2026